Copper(i) as a reducing agent for the synthesis of bimetallic PtCu catalytic nanoparticles - Fernández-Lodeiro, Adrián (2023)
This work was supported by the Spanish Government and the Spanish National Research Council (CSIC) (project PIE 201980E081). J. F. L. thanks FCT for the research contract through the Program DL 57/2016–Norma Transitória. This work was carried out in part through the use of the INL user facilities. The authors thank Dr Jamila Djafari for the conceptualization and design of the graphical abstract. We also thank Ramiro Martínez from Novozymes for the gift of enzymes. Publisher Copyright: © 2023 RSC